СИСТЕМНЫЙ АНАЛИЗ В СОВРЕМЕННОЙ МЕТОДОЛОГИИ - В. С. Хазов (SINAPS LLC, 2012)
System analysis itself is a breakthrough in science, and his best concept in the form of the theory of functional systems (FS), created by Academician Petr Kuzmich Anokhin, no doubt, is the value of a breakthrough in the search for etiology and pathogenesis of any disease. It is the opinion of the author, must now change the basic method of studying the disease - a method of clinic and anatomical comparisons, has lost its leading position. However, with the departure from the life of its creator, the theory of FS was not quite relevant and is not widely applied in scientific researches, which inhibited the development of the fundamentals of medicine. Author tries to show that without the use of FS theory to understand the essence of any pathology, and in particular, coronary heart disease will not succeed.